PROBLEMATIKA TRANSPARANSI KEUANGAN ZAKAT - Suginam; Sri Rahayu (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2021)
The potential of zakat in Indonesia is very large, so it needs to be managed professionally, safely, and regularly. In order for the potential of zakat to be collected, it must be realized through the performance of transparent zakat management institutions. Zakat is a mandatory worship in the life of the Muslim community in the social dimension of the people, this is in accordance with the third pillar of Islam and the recommendation for the importance of zakat contained in the word of Allah SWT in the Qur'an. Transparency is one of the factors that influence good governance in government institutions, both structural and non-structural. Zakat transparency is still considered very low and not optimal in zakat management institutions, it can be measured by the gap in potential and realization received and the level of public trust that is still low in zakat management institutions. The purpose of this study is to analyze the problems that occur in the transparency of zakat financial statements in order to find solutions to the problems. The research method is descriptive qualitative by analyzing the events and phenomena that occur. The method of analysis is done by means of observation, interviews and literature.